Women's Struggle In "The Color Purple" By Alice Walker: A Black Feminism Study - Febby Okta Novrianti; Merry Rullyanti; Dhanu Ario Putra (Literary Criticism, 2021)
The Color Purple by Alice Walker is a fiction novel that talks about African- American woman. The Color Purple was published in 1982 in New York USA, and made into a film in 1985 won the Pulitzer Prize awards. Based on the novel, African American women whose were struggle in the face of oppression that is dominated by men that occurred in America. This study aims to answer two formulations of the problem, namely; to determine the forms of oppression over women occur in the novel and to find out how the struggle of women in the novel. This study used a theoretical approach of Black Feminism belongs to Barbara Smith who saw a literary work of the whole social and historical context in which literary works are created as concept of criticism used by activists of black feminist at the time. The researcher used qualitative method to get validation data. The results of this study indicate that the form of oppression on women character in this novel is very diverse. There are three forms of oppression which is reflected in the novel that physical oppression, verbal oppression, and relational oppression. Then there are two forms of struggle carried out by the character of women is a direct confrontation and sisterhood bonding. Forms of fight carried out by Sofia and Shug Avery are directly. Sofia indicated the battle confrontation was clearly seen as the empowerment of struggle carried out by Shug Every became the main inspiration for the influence of character a female character in the vicinity. In the next fight Celie inspired by Shug Every also fight and was followed by Mary Agnes. Then do not miss the fight carried out by Netty. Keyword: Women, Struggle, Oppression, Black Feminism, The Color Purple